THE RECOGNITION OF HUMAN DIGNITY IN AFRICA: A CHRISTIAN ETHICS OF RESPONSIBILITY PERSPECTIVE - Villiers, Dawid Etienne de (Scriptura, 2010)
This article attempts, first of all, to define the concept of human dignity in tandem with a Christian ethics of responsibility. The views on human dignity, held by some proponents of a Christian ethics of responsibility, and a number of South African and Dutch theologians who participated in two joint consultations, are discussed and critically evaluated. Second, this article addresses the following question: "What does taking responsibility for the recognition and effective enhancement of human dignity in Africa entail?" The question is answered by drawing out the implications of four principles of a Christian ethics of responsibility, for the recognition and effective enhancement of human dignity in Africa.